From Surge to Stability: Trade Growth and Investment Limits in the Visegrád Four - Emy Sri Reskiyah; Andi Meganingratna (Budi Luhur Journal of Strategic & Global Studies, 2026)
Abstract: The Visegrád Group (V4), comprising the Czech Republic, Hungary, Poland, and Slovakia, has evolved from a political alliance into a significant subregional economic actor within the European Union (EU). While much research emphasizes post-2004 dynamics, the pre-accession trajectory and intra-V4 economic relations remain less systematically explored. This paper addresses this gap by comparing trade and foreign direct investment (FDI) across two phases, namely the pre-accession period (1995–2004) and the post-accession period (2005–2022). The study adopts a qualitative research design based on documentary analysis, thematic interpretation, and a strengths, weaknesses, opportunities, and threats (SWOT) framework, with descriptive indicators such as CAGR used only for contextual support. The findings indicate that intra-V4 trade is characterized by rapid pre-accession expansion followed by a more stable post-accession trajectory, while intra-V4 FDI integration remained limited and continued to be dominated by EU-15 economies. Interpreted through regionalism and spillover theory, the results suggest that functional spillover fostered lasting trade integration, whereas investment integration was constrained by structural asymmetries and competitive dynamics, thereby revealing the limits of subregional spillover within the EU framework. The study concludes that the V4’s long-term relevance depends on strengthening intra-regional investment, diversifying beyond manufacturing, and enhancing institutional coordination. Abstrak: Kelompok Visegrád (V4), yang terdiri dari Republik Ceko, Hongaria, Polandia, dan Slovakia, telah berevolusi dari aliansi politik menjadi aktor ekonomi subregional yang signifikan di dalam Uni Eropa (UE). Meskipun banyak penelitian menekankan dinamika pasca-2004, lintasan pra-aksesi dan hubungan ekonomi intra-V4 masih kurang dieksplorasi secara sistematis. Artikel ini membahas kesenjangan dengan membandingkan perdagangan dan investasi langsung asing (FDI) dalam dua fase, yaitu periode pra-aksesi (1995–2004) dan periode pasca-aksesi (2005–2022). Studi ini mengadopsi desain penelitian kualitatif berdasarkan analisis dokumen, interpretasi tematik, dan kerangka kerja kekuatan, kelemahan, peluang, dan ancaman (SWOT), dengan indikator deskriptif seperti CAGR hanya digunakan untuk dukungan kontekstual. Temuan menunjukkan bahwa perdagangan intra-V4 ditandai dengan ekspansi pra-aksesi yang cepat diikuti oleh lintasan pasca-aksesi yang lebih stabil, sementara integrasi FDI intra-V4 tetap terbatas dan terus didominasi oleh ekonomi UE-15. Diinterpretasikan melalui teori regionalisme dan spillover, hasilnya menunjukkan bahwa spillover fungsional mendorong integrase perdagangan yang berkelanjutan, sedangkan integrasi investasi dibatasi oleh asimetri struktural dan dinamika persaingan, sehingga mengungkapkan batasan limpahan subregional dalam kerangka Uni Eropa. Studi ini menyimpulkan bahwa relevansi jangka panjang V4 bergantung pada penguatan investasi intra-regional, diversifikasi di luar sektor manufaktur, dan peningkatan koordinasi kelembagaan.